Desafios e oportunidades na abertura do ambiente de contratação livre de energia elétrica no Brasil - Schmoller, Maria Cristina (2022)
The deregulation of the electricity markets around the world started about three decades ago. This deregulation focuses on bringing competition to both ends of the market, decentralizing the power-producing and commercialization sectors, and giving consumers more freedom to select their electricity sellers. The major goal of this research is to examine the future of the Brazilian electricity market through lessons learned from other countries and an investigation of recent proposals from institutions involved in the Brazilian sector. Bibliographic research is conducted to analyze the electricity market's deregulation process in six countries: the United Kingdom, Australia, Portugal, Spain, France, and the United States of America – the State of California. The analysis is then expanded to include (i) a historical assessment of the Brazilian electrical market, its agents, and institutions, as well as (ii) the most recent proposals (PL 414/21 and technical recommendations from ANEEL and CCEE) to support this deregulation process in Brazil. Given that each country has unique and distinct technical, economic, political, and regulatory characteristics, the analysis of the experiences of the governments that have already experienced the process of deregulating the electricity market clearly demonstrates that opening up the electricity market is valuable but, at the same time, insufficient. The outcomes of the literature review pointed to the need for more in-depth research on the role of the current regional distributors, including the dissociation of electricity transmission/distribution activities from electricity generation and commercialization activities and the balancing of the costs of supplier contracts in the transition from a regulated market to a competitive electricity market. In order to fill responsibilities that will be essential to this migration process, there is also a need to establish and maintain institutions and agents in the Brazilian electricity sector. Furthermore, given the inherent volatility of electricity prices associated with a renewable matrix, studies on the real effect of this volatility in the renewable Brazilian electricity matrix are critical.